Green microwave extraction of antioxidants and phenolic compounds from Moringa oleiferaleaf: An optimization study using response surface methodology - Cheong, T. K.; Siti Kholijah, Abdul Mudalip; N. A., Hashim; M. N., Khatiman; Rohaida, Che Man; Siti Zubaidah, Sulaiman; Shalyda, Md Shaarani (Universiti Malaysia Pahang, 2024)
Moringa oleifera is a good source of nutrition and very beneficial for health improvement. This study aimed to optimize the process parameters for the extraction of bioactive substances fromM. oleiferaleaf using microwave-assisted extraction (MAE). The response surface methodology (RSM) based on Box-Behnken designs (BBD) was used to optimizethe process parameters including solid-to-solvent ratio (1 to 3 g/100 mL), microwave power (100 to 200 W), and extraction time (15 to 25 min) on the total phenol content (TPC) and antioxidant activity (AA). The optimum conditions were 2.01 g/100 mL solid-to-solvent ratio, 152.7 W microwave power, and 20.54 min extraction time to obtained to obtain the optimum TPC and AA. The optimum TPC and DPPH were 529.801 mg GAE/g dry sample and 87.67%, respectively. The results were successfully fitted into the second-order polynomial model with R2values of 0.9958 and 0.9865, respectively. The predicted TPC and AA deviate from the experimental data by 1.40% and 2.69%, respectively. Thus, the model accuracy is proved for the modelingof M. oleiferaleaves extraction by MAE